Cholestatic Syndrome - Zhen, Felipe [UNESP]; Sugisawa Kay Locatelli, Susan; Pedrotti Locatelli, Felipe; Klug Pimentel, Silvania; Abreu, Phillipe (Springer Nature, 2025)
The cholestatic syndrome is defined as an increase in serum direct bilirubin caused by the accumulation of bile in the liver, starting from the hepatocyte and extending to the bile duct near the duodenum. The syndrome can be classified into intrahepatic and extrahepatic categories based on its underlying causes.